The Strategic Alliance of Small Enterprises is the Most Effective Way to Support them and Get Rid of their Financing Problems- Examples of International Institutions - Zohra, Dr. Gramez Fatima (The journal of contemporary issues in business and government, 2023)
Throughout this study, It is dealt with the role and importance of the small enterprises in the economic development for countries and the challenges affronted by such institutions in an unstable environment ,and the need to change thought trend to cope with such changes by way of adopting the alliance strategy which would result in a bunch of advantages and objectives for these institutions. By way of exemplification, an example of the strategic alliance was provided for some notable international companies and institutions in link withsome small institutions and the alliance results which were realized. It was realized that his strategic alliance between the greatest institutions ,on the one hand and the small and medium ones, on the other hand would be regarded as a forceful means to preserve the remaining of these institutions and support them to get developed through accompanying them and supporting them financially.